Characteristics of hypertension in obstructive sleep apnea: An Asian experience. Issue 3 (11th March 2021) - Hoshide, Satoshi; Kario, Kazuomi; Chia, Yook‐Chin; Siddique, Saulat; Buranakitjaroen, Peera; Tsoi, Kelvin; Tay, Jam Chin; Turana, Yuda; Chen, Chen‐Huan; Cheng, Hao‐Min; Huynh, Van Minh; Park, Sungha; et al.
Abstract: Obstructive sleep apnea (OSA) is a risk of hypertension and is associated with cardiovascular disease (CVD) incidence. In Asian countries, the prevalence of OSA is high, as in Western countries. When blood pressure (BP) is evaluated in OSA individuals using ambulatory BP monitoring (ABPM), the BP phenotype often indicates abnormal BP variability, such as increased nighttime BP or abnormal diurnal BP variation, that is, non‐dipper pattern, riser pattern, and morning BP surge, and all these conditions have been associated with increased CVD events. Asians have a higher prevalence of increased nighttime BP or morning BP surge than Westerners. Therefore, this review paper focused on OSA and hypertension from an Asian perspective to investigate the importance of the association between OSA and hypertension in the Asian population. Such abnormal BP variability has been shown to be associated with progression of arterial stiffness, and this association could provoke a vicious cycle between abnormal BP phenotypes and arterial stiffness, a phenomenon recognized as systemic hemodynamic atherothrombotic syndrome (SHATS). OSA may be one of the background factors that augment SHATS. An oxygen‐triggered nocturnal oscillometric BP measurement device combined with a pulse oximeter for continuous SpO2 monitoring could detect BP variability caused by OSA. In addition to treating the OSA, accurate and reliable detection and treatment of any residual BP elevation and BP variability caused by OSA would be necessary to prevent CVD events. However, more detailed detection of BP variability, such as beat‐by‐beat BP monitoring, would further help to reduce CV events.